Between play and the quotidian: inscriptions of monstrous characters on the racialised bodies of children. Issue 2 (4th March 2017) - Rosen, Rachel
Abstract: Despite critiques pointing out that racism has become normalised in early childhood settings, relatively little attention has been paid in such contexts to the everyday practices in which racial inequities are made. In seeking to interrogate the ways in which racism roosts in the routine, this article interrogates quotidian responses to children's playful activity, drawing on data generated in an ethnographic study in a London-based nursery. The article argues that the imaginative characters players embody become 'fixed' on particular children – when these characters coincide with reified assumptions about the raced, classed, and gendered body – whilst serving as mobile resources for others. Such reification, which is a concentration of complex historic and contemporary social relations in the political economy, is not only harmful and unjust but limits understandings of racialisation and inequity.